Interactive Ar-Edugame On Learning Indonesian Traditional Weapons - Negara, Mawardi Ganda; , Endah Sudarmilah, S.T., M.Eng (2015)
Traditional weapons is a product that is closely related to the culture of a society. Besides being used to shelter from enemy attack, the traditional weapon was also used in farming and hunting activities. More than function, traditional weapon has become the identity of a nation that helped enrich the cultural treasures of the archipelago. Education in Indonesia is guided by a new curriculum called Curriculum 2013. One of the material on curriculum lead students to learn about Indonesian Traditional Weapons, It make students hard to imagine the figure of Indonesian Traditional Weapons. Reflecting on the problems arising from the curriculum of 2013, researchers set up a learning method by combining AR with Educational game in presenting the material of Indonesian culture diversity, especially for the traditional weapons. This research done by collecting research data in SDIT Muhammadiyah Al-Kautsar Surakarta, and from the internet. The results of the research was an Educational game with the Augmented Reality support to learn about Indonesian Traditional Weapons, that easy to play and learn for children and teacher, namely "GatotVentura".